Not What I Expected: Early Career Prospects of Doctoral Graduates in Academia - Etmanski, Brittany; Walters, David; Zarifa, David (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2017)
Various studies acknowledge the uncertainty many doctoral graduates face when beginning their search for full-time employment within the academic sector. Recent graduates face a job market where the likelihood of obtaining full-time permanent positions in academia is perceived to be declining, and the mobility of graduates within the sector is unclear. Drawing on Statistics Canada’s 2013 National Graduates Survey, this paper assesses whether graduates who pursued a doctoral degree to become a full-time professor achieved their goal within three years of graduation. The results suggest that although a large portion of doctoral graduates pursued their degrees to become full-time professors, relatively few reported obtaining such positions within three years of graduation, regardless of field of study.